Relationship of Husband's Assistance to the Level of Mother's Anxiety in the Active Phase of the First Stage of Normal Labor Process - Moh Wafri Matorang; Nurwahita (Institut Citra Internasional, 2025)
Spontaneous labor that is low-risk during the early phase often remains so throughout the process. Anxiety, defined as an unclear fear not based on the situation, commonly affects mothers during childbirth. Support from a husband can significantly reduce this anxiety, helping mothers feel more at ease. This study aimed to determine the relationship between husband’s assistance and maternal anxiety levels during the active phase of the first stage of normal labor at Makassar City Hospital. This research used an observational analytic design with a cross-sectional approach. The sample consisted of 60 mothers who had normal deliveries at Makassar City Hospital in December, selected through accidental sampling. Data was collected using questionnaires and analyzed with the chi-square test. The results showed that husband or family assistance with moderate maternal anxiety was reported by 53 respondents (88.3%). Good assistance was associated with severe anxiety in only 2 respondents (3.3%), while adequate assistance with moderate anxiety was seen in 3 respondents (5.0%). Limited assistance with moderate anxiety was reported by 2 respondents (3.3%).The p-value obtained was 0.003, indicating statistical significance (p < 0.05), which leads to the conclusion that there is a significant relationship between husband’s assistance and maternal anxiety levels in the active phase of the first stage of labor.Thus, it can be concluded that the presence and support of a husband during labor can play a crucial role in reducing maternal anxiety during childbirth at Makassar City Hospital.